2021
DOI: 10.1101/2021.02.11.21251562
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population Age-Ineligible for COVID-19 Vaccine in the United States: Implications for State, County, and Race/Ethnicity Vaccination Targets

Abstract: Background: We examined the geographic and racial/ethnic distribution of the SARS-CoV-2 vaccine age-ineligible population (0-15 years old) in the U.S., and calculated the proportion of the age-eligible population that will need to be vaccinated in a given geo-demographic group in order to achieve either 60% or 75% vaccine coverage for that population as a whole. Methods: US Census Bureau population estimates for 2019 were used to calculate the percent vaccine ineligible and related measures for counties, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Thus, it can be concluded that the best method to prevent hospitalization and death from COVID-19 would be to receive one of the vaccines that have been recognized by a reputable health agency, such as the WHO [ 160 ]. The unprecedented ability to receive protection against COVID-19 hospitalization and death has unfortunately been undermined by rampant misinformation regarding COVID-19 [ 161 , 162 ] coupled with vaccine inequity and ineligibility worldwide [ 116 , 163 ]. Receiving a vaccine as soon as possible when eligible will help women engage more safely in PA due to the reduced risk of acute COVID-19 infection and complications if exposed to SARS-CoV-2 ( Figure 3 ).…”
Section: Covid-19 Vaccination and Its Relevance To Women’s Health And Maintaining An Active Lifestylementioning
confidence: 99%
“…Thus, it can be concluded that the best method to prevent hospitalization and death from COVID-19 would be to receive one of the vaccines that have been recognized by a reputable health agency, such as the WHO [ 160 ]. The unprecedented ability to receive protection against COVID-19 hospitalization and death has unfortunately been undermined by rampant misinformation regarding COVID-19 [ 161 , 162 ] coupled with vaccine inequity and ineligibility worldwide [ 116 , 163 ]. Receiving a vaccine as soon as possible when eligible will help women engage more safely in PA due to the reduced risk of acute COVID-19 infection and complications if exposed to SARS-CoV-2 ( Figure 3 ).…”
Section: Covid-19 Vaccination and Its Relevance To Women’s Health And Maintaining An Active Lifestylementioning
confidence: 99%